A novel CFD-DEM upscaling method for prediction of scour under live-bed conditions. (15th January 2021) - Yazdanfar, Z.; Lester, Daniel; Robert, Dilan; Setunge, Sujeeva
Abstract: Despite intensive research efforts, the accurate modelling and prediction of bridge pier scour is an outstanding challenge due to the complexities arising from the detailed interactions between granular and fluid mechanics in the riverbed. Pier scour predictions based on empirical formulas are used in conventional bridge design codes which fail to realistically account for these interactions, and thus fail to facilitate pier design optimization. A critical step towards optimal pier design is an improved physical understanding of detailed mechanisms of the scour process and the development of appropriate modelling techniques to resolve these mechanisms in engineering applications. In this study, a combination of computational fluid dynamics (CFD) and discrete element modelling (DEM) is used to improve physical understanding of the scour process, including detailed interactions between river hydrodynamics, transport of suspended particles, and granular mechanics of the riverbed. As CFD-DEM models of turbulent hydrodynamics coupled with densely packed granular assemblies are computationally expensive, it is currently not feasible to accurately model scour in macroscopic engineering applications. To address this problem, we propose a novel upscaling methodology based on highly-resolved microscale simulations that significantly reduces the computational overhead, facilitating macroscopic prediction of scour under live-bed conditions. Predictions of scour initiation, rate and extent from these microscale simulations have been validated against previously published experimental data. Results indicate that the microscale model is reasonably capable of predicting the scour initiation as well as the equilibrium scour depth. This upscaling model provides a viable methodology for the macroscopic prediction of scour in engineering applications with modest computational resources. Highlights: A novel upscaling method is presented for the macroscopic prediction of live-bed scour using modest computational resources. It uses computational fluid dynamics (CFD) and discrete element modelling (DEM) to resolve the fluid and particle mechanics. Upscaling is achieved via a microscopic scour model which is governed by fluid shear stress and particle-bed collisions. Once populated, the scour function facilitates macroscopic scour prediction using only CFD simulation and particle tracking.